Bimbingan Teknis Perencanaan Perkerasan Jalan pada Kabupaten Aceh Timur - Salsabila, Shafira; Bukit, Ipak Neneng Mardiah; Masthura, Lely; Fahriana, Nina; Ardhyan, Muhammad Zacky (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
Road infrastructure development in rural areas is a key factor in driving economic growth and increasing community accessibility to basic services. Gampong Pante Kera, Simpang Jernih District, East Aceh Regency, is one of the areas that needs to improve the quality of road infrastructure. For this reason, this community service activity was carried out to provide Technical Guidance on Road Paving Planning to village officials and community representatives, so that they have adequate skills in planning and implementing road paving according to local conditions and applicable technical standards. The activity method includes the coordination stage with village officials, technical training on road paving concepts and techniques, preparation of Detailed Engineering Design (DED), 2D perspective design, and preparation of Budget Plan (RAB). In addition, monitoring and evaluation were carried out to ensure that implementation went according to plan. The results of the activity showed that village officials and community representatives had significant improvements in understanding and technical skills, allowing them to be more active and independent in the process of planning and building village roads. With this technical guidance, it is hoped that infrastructure development in Gampong Pante Kera can be carried out effectively, efficiently, and sustainably, to improve the welfare of the local community.